2008
DOI: 10.1200/jco.2007.13.5517
|View full text |Cite
|
Sign up to set email alerts
|

Toremifene Improves Lipid Profiles in Men Receiving Androgen-Deprivation Therapy for Prostate Cancer: Interim Analysis of a Multicenter Phase III Study

Abstract: Purpose-Androgen-deprivation therapy (ADT) is associated with greater risk of incident coronary heart disease and hospital admission for myocardial infarction; treatment-related increases in serum lipids may contribute to greater cardiovascular disease risk. We evaluated the effects of toremifene, a selective estrogen-receptor modulator, on fasting serum lipid levels in men receiving ADT for prostate cancer.Patients and Methods-In an ongoing, multicenter, double-blind, placebo-controlled phase III fracture-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…27,34,35 Serum HDL decreased by ~5% in 12 months in one study. 36 There was no change in serum LDL in 3-6 months of therapy. 34,35 However, there was one study which showed a rise in LDL of 7% in the first 3 months.…”
Section: Lipid Profilementioning
confidence: 87%
“…27,34,35 Serum HDL decreased by ~5% in 12 months in one study. 36 There was no change in serum LDL in 3-6 months of therapy. 34,35 However, there was one study which showed a rise in LDL of 7% in the first 3 months.…”
Section: Lipid Profilementioning
confidence: 87%
“…12 Conversely, a large, recent study showed a decrease in HDL and an increase in low-density lipoprotein (LDL), triglycerides and total cholesterol with 12-month use of ADT. 13 Prior studies have generally featured small sample sizes, and have not consistently accounted for patient medication use, smoking history, body mass index (BMI) and previous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Toremifene significantly improved serum lipid profiles in postmenopausal women [40][41][42][43]. In an interim analysis of a large, multicenter, randomized, controlled study of men receiving ADT for prostate cancer, toremifene significantly decreased total cholesterol, LDL cholesterol, and triglycerides, and increased HDL cholesterol [44]. The beneficial effects of toremifene on lipid profiles provide a strong rationale to conduct exploratory analyses of cardiovascular outcomes when the ongoing fracture prevention study is completed.…”
Section: Survivorsmentioning
confidence: 99%